2017
DOI: 10.1101/235879
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutations alter RNA-mediated conversion of human prions

Abstract: Abstract:Prion diseases are connected with self-replication and self-propagation of mis-folded proteins.The rate-limiting factor is the formation of the initial seed. We have recently studied early stages in the conversion between functional PrP C and the infectious scrapie PrP SC form, triggered by the binding of RNA. Here, we study how this process is modulated by the prion sequence. We focus on residues 129 and 178, which are connected to the hereditary neurodegenerative disease Fatal Familial Insomnia.peer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
3
2
0
Order By: Relevance
“…Except for the large structural change of the α2 C-terminus, we also observed that α1 in AMD1 and AMD6 is partially unfolded, indicating that α1 may also play an important role in the pHinduced PrP misfolding, since previous studies have shown that α1 can act as a gate-keeper 39,40 by preventing the α2-α3 subdomain from becoming hydrated, and it tends to unravel under the RNA-induced PrP misfolding. 41,42 Meanwhile, as we observed in run 3, we also find that in the trajectories AMD2 and AMD4, typical β-structures are newly formed at the β2-α2 loop, which was not observed in the works of Kamp/ Daggett. 23,27 This finding further supports that the β2-α2 loop can also serve as an important site for PrP misfolding, since single residue substitution of this region in mouse PrP Sc can reduce or prevent prion conversion in vitro.…”
Section: ■ Results and Discussionsupporting
confidence: 50%
“…Except for the large structural change of the α2 C-terminus, we also observed that α1 in AMD1 and AMD6 is partially unfolded, indicating that α1 may also play an important role in the pHinduced PrP misfolding, since previous studies have shown that α1 can act as a gate-keeper 39,40 by preventing the α2-α3 subdomain from becoming hydrated, and it tends to unravel under the RNA-induced PrP misfolding. 41,42 Meanwhile, as we observed in run 3, we also find that in the trajectories AMD2 and AMD4, typical β-structures are newly formed at the β2-α2 loop, which was not observed in the works of Kamp/ Daggett. 23,27 This finding further supports that the β2-α2 loop can also serve as an important site for PrP misfolding, since single residue substitution of this region in mouse PrP Sc can reduce or prevent prion conversion in vitro.…”
Section: ■ Results and Discussionsupporting
confidence: 50%
“…The high flexibility of this region can be seen also in Figure 5 where we show the root-mean-square fluctuation (RMSF) of residues as measured over the last 120 μs of our simulations. Consistent with earlier work, 9 we find an increased flexibility and partial unwinding of helix B and, to a lesser degree, the same for helix C, for all four systems, and only small differences between control and complex with RNA; see Table 2.…”
Section: Effect Of Poly-a-rna and Sequencesupporting
confidence: 92%
“…The 10 highest scoring docked systems for each of the four targets were collected and examined for common regions of protein−RNA interaction. As in our previous studies 9,30 we found three main binding sites: binding site 1 (residues 21−31), binding site 2 (residues 111−121), and binding site 3 (residues 144−155). For the wild type 129M-178D and the mutant 129V-178N, all three binding sites were found, while in the wild-type variant 129V-178D binding site 3 is lost, and in the mutant 129M-178N the binding sites 1 and 2 are lost.…”
Section: Model Preparationsupporting
confidence: 88%
See 2 more Smart Citations